Energy and exergy equilibrium analysis of Stirling-type thermal compressor (STC)—The core part in thermal-driven Vuilleumier machines. (1st November 2019) - Wang, Jue; Xi, Xiaotong; Luo, Kaiqi; Chen, Liubiao; Wang, Junjie; Zhou, Yuan
Highlights: Energy and exergy equilibrium relationships of STC were studied in thermodynamics. A three-order model was built to verify the equilibrium relationship. Parameter effects on efficiency, loss and thermal-driven characteristic were studied. Optimization of external loss were made and the exergy efficiency of 60% was obtained. Abstract: The Stirling-type machines show high-potential efficiency in energy conversion process. The direct conversion process from heat at relative high temperature to cooling power can be realized by the thermal-driven Stirling refrigerator, so called Vuilleumier refrigerator. However, the relative low efficiency of the actual Vuilleumier machine (including refrigerator and heat pump) caused by various losses hinders itself further development. The Stirling-type thermal compressor (STC) is the core heat-work conversion part in the Vuilleumier machine and most exergy loss is concentrated here. For better understanding the internal heat-work conversion and loss process in STC, firstly, the thermodynamic equilibrium relationships of energy and exergy in STC were discussed. Secondly, a reliable three-order model of STC was built and the RC-load operation and no-load operation were compared under the instruction of the equilibrium relationships above. Thirdly, detailed parameter effects on the output performance, loss composition, exergy efficiency and thermal-driven characteristic were carried out. At last, the optimization principle of external loss in STC was studied, which could improve the STC's exergy efficiency to 60%.